Compositional, genetic and functional characterization of soil culturable microbial communities in polychlorinated dibenzo-p-dioxins/furans contaminated soil - Mahfouz, Sabrin; Mansour, Gaytha; Hanano, Abdulsamie (Frontiers in Environmental Science, 2022)
Dioxins (PCDD/Fs) are one of the most toxic environmental pollutants known to date. Due to their structural stability and extreme hydrophobicity dioxins persist in the ecosystems and can be bioaccumulated to critical levels in both human and animal food chains. Soils are the most important reservoirs of dioxins, thus soil microbes are highly exposed to dioxins, impacting their diversity, genetics and functional characteristics. To experimentally evaluate these effects, the diversity and functionality of soil microbes were assessed in seven local sites potentially exposed to PCDD/Fs. Concentration of dioxins in soils samples was firstly determined and the soils cultivable microbes were identified and molecularly characterized as a function of their in vitro ability to degrade the TCDD. Our results revealed that the diversity of microbial communities largely varied among the sites and was likely inversely proportional to their level of contamination with PCDD/Fs. Furthermore, the genetics profiling of dioxin-degrading bacteria revealed that the Cytochrome P450 CYPBM3-positive species largely belong to the genus Bacillus and were randomly distributed among the soils samples, while the angular dioxygenase (AD)-positive species were mainly found in highly polluted soils with a major presence of the genus Pseudomonas. Finally, the functionality of dioxin-biodegrading genes (AD or CYPBM3), was confirmed by the ability of bacteria to consume 2,3,7,8-TCDD, and this was synchronized with an induced level of both pathways. Our results suggest that different dioxin-metabolizing pathways exist under the same environmental conditions and work differentially for an effective removal of PCDD/Fs.